Tritium retention measurements by accelerator mass spectrometry and full combustion of W-coated and uncoated CFC tiles from the JET divertor. (23rd March 2016) - Stan-Sion, C.; Bekris, N.; Kizane, G.; Enachescu, M.; Likonen, J.; Halitovs, M.; Petre, A.
Abstract: Accelerator mass spectrometry (AMS) and the full combustion method (FCM) followed by liquid scintillation counting were applied to quantitatively determine the tritium retention in the tungsten-coated carbon fibre composites (CFC), in comparison to uncoated CFC tiles from the JET divertor. The tiles were adjacent and exposed to plasma operations between 2007 and 2009. The tritium depth profiles are showing that the tritium retention on the W-coated tile was reduced by a factor of 13.5 in comparison to the uncoated tile whereas the bulk tritium concentration is approximately the same for both tiles.